Media Pembelajaran Berbasis Adobe Animate Mata Pelajaran IPAS Kelas V SD Negeri Tlogosari Kulon 05 Efektif dan Tingkatkan Hasil Belajar - Laysa Astri Rosemarry; Barokah Isdaryanti (Postgraduate, University of Mataram, 2024)
IPAS learning carried out at SD Negeri Tlogosari Kulon 05 experienced a decrease in learning outcomes marked by less than optimal KKTP results so that researchers conducted research related to learning media development. This study aims to develop Adobe Animate-based learning media and analyze the feasibility and effectiveness of Adobe Animate-based learning media. This research includes development research (Research and Development) with the ADDIE model. The subjects of this study were fifth grade students of SD Negeri Tlogosari Kulon 05. The results of this study developed learning media with the ADDIE model; Adobe Animate-based learning media are very feasible to implement with a percentage of material expert assessment of 91.6% and media experts 93.75%; and the effectiveness of learning media is tested with the results of the mean difference test by obtaining a sig (2-tailed) value of 0.000 which means that there is a significant difference in the average results of the pretest and posttest so that learning media can improve learning outcomes. It is concluded that Adobe Animate-based media is feasible and effective in learning IPAS in grade V of SD Negeri Tlogosari Kulon 05 which is known from the increase in learning outcomes